2014
DOI: 10.1016/j.bpobgyn.2013.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The content and delivery of psychological interventions for perinatal depression by non-specialist health workers in low and middle income countries: A systematic review

Abstract: Psychological interventions delivered by non-specialist health workers are effective for the treatment of perinatal depression in low- and middle-income countries. In this systematic review, we describe the content and delivery of such interventions. Nine studies were identified. The interventions shared a number of key features, such as delivery provided within the context of routine maternal and child health care beginning in the antenatal period and extending postnatally; focus of the intervention beyond th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(144 citation statements)
references
References 33 publications
5
136
1
2
Order By: Relevance
“…The search strategies are available in the Supplemental Appendix. In addition, the bibliographies of systematic reviews of psychological treatments delivered by NSPs in LMICs were also considered (Chowdhary et al 2014, Clarke et al 2013, Rahman et al 2013, van’t Hof et al 2011, van der Waerden et al 2011, van Ginneken et al 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The search strategies are available in the Supplemental Appendix. In addition, the bibliographies of systematic reviews of psychological treatments delivered by NSPs in LMICs were also considered (Chowdhary et al 2014, Clarke et al 2013, Rahman et al 2013, van’t Hof et al 2011, van der Waerden et al 2011, van Ginneken et al 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Opportunities for improved co-ordination are offered by using such visits to give advice on nutrition, child health, child development programmes, positive parenting programmes, vaccination programmes, routine childbirth education sessions and community health programmes. 389 Group interventions can seek to achieve improved acceptability and feasibility by being offered in conjunction with individual health-care appointments, as in the CenteringPregnancy model.…”
Section: Support To Providersmentioning
confidence: 99%
“…In fact, research has demonstrated the effectiveness of this type of intervention in treating perinatal depression and common mental disorders (depressive and anxiety disorders) in other countries, including China and India. 33,34 Future intervention research may consider training lay counselors to reach out to and treat PPD among Vietnamese American mothers. Moreover, practitioners and researchers also need to understand the Vietnamese American mothers' viewpoints about the definition, causes, and symptoms of PPD, as illustrated in this study.…”
Section: Implications For Behavioral Healthmentioning
confidence: 99%